2022
DOI: 10.3389/fchem.2022.911453
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel α-Aminophosphonates with Hydrazone as Potential Antiviral Agents Combined With Active Fragment and Molecular Docking

Abstract: A series of novel α-aminophosphonate derivatives containing hydrazone were designed and synthesized based on active fragments. Bioassay results demonstrated that title compounds possessed good activities against tobacco mosaic virus. Among them, compounds 6a, 6g, 6i, and 6j were equivalent to the commercial antiviral agents like dufulin. On structure optimization-based molecular docking, compound 6k was synthesized and displayed excellent activity with values of 65.1% curative activity, 74.3% protective activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Several α -aminophosphonate derivatives, exhibiting interesting biological properties, have previously been synthesized ( El-Boraey et al, 2015 ; Gundluru et al, 2021 ; Tian et al, 2022 ). Many studies have reported their potential as antiviral agents ( Hu et al, 2008 ; Song et al, 2010 ; Amira et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several α -aminophosphonate derivatives, exhibiting interesting biological properties, have previously been synthesized ( El-Boraey et al, 2015 ; Gundluru et al, 2021 ; Tian et al, 2022 ). Many studies have reported their potential as antiviral agents ( Hu et al, 2008 ; Song et al, 2010 ; Amira et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The treatment, protection, and passivation of compound 60 against TMV were 33.2%, 65.1%, and 45.7%, while, for compound 61 against TMV, they were 74.3%, 78.7%, and 94.3%. Molecular docking found that benzothiazole rings are important for the antiviral activity of these compounds, and the hydrazone’s structure can affect the compounds’ antiviral activity [ 100 ]. The combination of benzothiazoles with diesters or amino phosphonate had good antiviral activity, which showed the advantage of the skeleton structure in antiviral activity.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Compounds containing an aminophosphonic unit display a wide spectrum of biological activity ( Figure 4 ), e.g., antiproliferative [ 28 , 29 , 30 , 31 ], antimicrobial [ 32 , 33 , 34 ], antiviral [ 35 , 36 ], antioxidant [ 37 , 38 , 39 , 40 ], anti-inflammatory [ 37 , 41 , 42 ] and they act as inhibitors of various enzymes such as acetylcholinesterase [ 43 , 44 , 45 ], aminopeptidases [ 46 , 47 ] or α-glucosidase [ 48 ].…”
Section: Introductionmentioning
confidence: 99%